If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying w + 5 = 3w + 1 Reorder the terms: 5 + w = 3w + 1 Reorder the terms: 5 + w = 1 + 3w Solving 5 + w = 1 + 3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3w' to each side of the equation. 5 + w + -3w = 1 + 3w + -3w Combine like terms: w + -3w = -2w 5 + -2w = 1 + 3w + -3w Combine like terms: 3w + -3w = 0 5 + -2w = 1 + 0 5 + -2w = 1 Add '-5' to each side of the equation. 5 + -5 + -2w = 1 + -5 Combine like terms: 5 + -5 = 0 0 + -2w = 1 + -5 -2w = 1 + -5 Combine like terms: 1 + -5 = -4 -2w = -4 Divide each side by '-2'. w = 2 Simplifying w = 2
| 3p^2=-10p-3 | | -12x^2-48x+60=0 | | -12x+6*4=30 | | x/3=5/7 | | x-2y^2=-2 | | aw+at-h=y*a | | x/7=9/9 | | M/3+2=17 | | a/3-17=14 | | -37x=-146 | | P/4+13=21 | | x/4=6/8 | | 12(x-5)=6*7 | | 4(b-8)=5(b+3) | | x^2+2x+11= | | -7*(-28+6y)+5y=-1 | | -7*(28+6y)+5y=-1 | | 5x^3-30x=0 | | 3x+23=180 | | 3x+23=90 | | 3x+23=2x+12 | | 3x^4+15x^2-42=0 | | 3x^4-15x^2-42=0 | | -4x+(-2x)+6=9 | | y^2-9y-36= | | 9(x+3)-18=-90 | | -4c(-c-24)=-4c-24 | | 120+0.40x=50+0.60x | | 12f*5= | | 5x-16=90 | | x+49+7=x | | X-33=15 |